Handle with care: Jury deliberation and demeanour-based assessments of witness credibility. (October 2022) - Chalmers, James; Leverick, Fiona; Munro, Vanessa E.
It is unclear how effectively jurors perform their task of assessing witness credibility. Drawing on evidence from a mock jury study involving 863 mock jurors deliberating across 64 juries, and building on existing research, this paper explores juries' reliance on demeanour. While jurors make use of factors which the research literature suggests are often appropriate credibility markers, for example external consistency of accounts, there is cause for concern over the nuance with which jurors apply those assessments in high stakes contexts. The manner in which jurors look to manner of delivery as evidence of credibility is also problematic. The paper makes the case for a more circumspect approach towards jurors' use of demeanour assessments. At a minimum, this requires that judicial directions no longer advocate their reliability, but remind jurors of the complexities associated with such assessments and the need to treat any conclusions grounded on presentational cues with caution.